Hubungan Safety Promotion dengan Perilaku Aman pada Pekerja Konstruksi Proyek Pembangunan - Andriyadi, Yakub; Setyowati, Dina Lusiana; Ifroh, Riza Hayati (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2021)
Background: As much as 88% of work accidents are caused by unsafe behavior. Encouraging a safety culture through a behavior-based safety approach could prevent work accidents. PT X's Mulawarman University building construction project reporting from June 2018 to November 2019, there were 13 accidents. It is crucial to encourage a behavior-based safety approach by promoting occupational safety and health to prevent accidents in the workplace. The research objective was to determine the relationship between safety promotion consisting of safety talk, K3 training, supervision with safe behavior in PT X construction workers, and the Mulawarman University building construction. Method: This study used a quantitative approach with a cross-sectional method. The population of this study was all employees of PT X, with a sample of 138 workers using probability sampling techniques with a proportionate stratified random sampling method. The data source obtained from a questionnaire that previously tested the validity with a value> 0.361 and reliability with a value of safe behavior (0.892), safety talk (0.920), training (0.920), and supervision (0.739). Bivariate analysis using Spearman Rank test and multivariate analysis using Binary Logistics Regression test (significant level 0.05). Results: The results of this study indicate that there is a relationship between safety promotion which consists of a safety talk (p-value = 0.001), training (pvalue = 0.009) and supervision (p-value = 0.001) with safe behavior in PT X building construction workers. The variable that has the level of influence on the safe behavior of workers is the supervision variable. Therefore, efforts to improve by having a commitment through safety promotion activities and involving workers in implementing safety in the company environment are critical.